2021
DOI: 10.1371/journal.pone.0245760
|View full text |Cite
|
Sign up to set email alerts
|

Towards the restoration of ancient hominid craniofacial anatomy: Chimpanzee morphology reveals covariation between craniometrics and facial soft tissue thickness

Abstract: In modern humans, facial soft tissue thicknesses have been shown to covary with craniometric dimensions. However, to date it has not been confirmed whether these relationships are shared with non-human apes. In this study, we analyze these relationships in chimpanzees (Pan troglodytes) with the aim of producing regression models for approximating facial soft tissue thicknesses in Plio-Pleistocene hominids. Using CT scans of 19 subjects, 637 soft tissue, and 349 craniometric measurements, statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The present study identified another set of predictable relationships, this time for predicting pronasale position in a similar way. Studies such as these are revealing that regression models actually outperform averages [ 18 , 38 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study identified another set of predictable relationships, this time for predicting pronasale position in a similar way. Studies such as these are revealing that regression models actually outperform averages [ 18 , 38 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Campbell et al [38] showed facial soft tissue thicknesses covary with craniometric dimensions in chimpanzees, and that this allows for predictions of soft tissues from cranial measurements more precisely than by using averages of thicknesses. The present study identified another set of predictable relationships, this time for predicting pronasale position in a PLOS ONE similar way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation